2013
DOI: 10.3390/nu5125097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Breakfasts (with or without Eggs) on Body Weight Regulation and Blood Lipids in University Students over a 14-Week Semester

Abstract: The effects of breakfast type on body weight and blood lipids were evaluated in university freshman. Seventy-three subjects were instructed to consume a breakfast with eggs (Egg Breakfast, EB, n = 39) or without (Non-Egg Breakfast, NEB, n = 34), five times/week for 14 weeks. Breakfast composition, anthropometric measurements and blood lipids were measured at multiple times. During the study, mean weight change was 1.6 ± 5.3 lbs (0.73 ± 2.41 kg), but there was no difference between groups. Both groups consumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Large epidemiological works have been conducted to investigate the effect of egg intake on blood cholesterol levels and risk of CVD in children [123], young people [16, 20, 47, 124], women [1214, 125, 195, 196], men [1214, 125, 195199], and older adults [1214, 125, 195200]. Some have shown that egg consumption did influence the blood cholesterol level but did not increase the risk of CVD in healthy people.…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%
“…Large epidemiological works have been conducted to investigate the effect of egg intake on blood cholesterol levels and risk of CVD in children [123], young people [16, 20, 47, 124], women [1214, 125, 195, 196], men [1214, 125, 195199], and older adults [1214, 125, 195200]. Some have shown that egg consumption did influence the blood cholesterol level but did not increase the risk of CVD in healthy people.…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%
“…Consumption of eggs for breakfast has additionally been shown to increased satiety in overweight/obese women [ 154 ] and healthy men [ 155 ] when compared to a bagel breakfast, while also promoting weight loss and reductions in daily caloric intake [ 155 , 156 ]. Increased satiety from egg consumption has also been observed in young adults [ 157 ]. Together, these findings suggest that egg consumption may improve inflammation in overweight/obese individuals undergoing weight loss—either through direct action of bioactive components or indirect action of promoting satiety, weight loss, and restoration of adipose tissue function.…”
Section: Effects Of Egg Intake On Inflammation In Human Populationmentioning
confidence: 99%
“…Of the more recent studies completed ( Table 2 ), five of the seven studies have shown no adverse effects on the lipid profile following a high egg intake [ 66 , 67 , 68 , 70 , 71 ] and two have shown improvements in circulating lipids with an increased egg consumption [ 61 , 69 ].…”
Section: Controlled Prospective Studies Of the Effects Of A High Ementioning
confidence: 99%